Customer Trust In Marketplace Purchases: A Systematic Literature Review - Anggi Saputra; Abror Abror; Zul Afdal (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2025)
Trust is a crucial factor in online business because it facilitates the transaction process by making buyers willing to accept and not doubt the actions of online sellers. Therefore, this systematic literature review aims to comprehensively examine how consumer trust influences purchasing behavior on marketplaces. A literature review from databases ScienceDirect, focusing on peer-reviewed articles and empirical studies from 2020 to 2026 was conducted from Q1 and Q2 indexed journals. The PRISMA flow diagram guided the process to ensure that the research process includes structured data, from identification to the presentation of results and supported bibliometric analysis using VOSviewer. A defined search criteria after thorough analysis, only 15 were suitable for synthesis and reporting. The Mendeley referencing tool and Microsoft Excel were instrumental in facilitating the analysis. The findings from the literature review indicate that customer trust is a multidimensional construct at the core of digital market sustainability, linking technological innovation, ethical considerations, regulatory frameworks, and business strategies. This literature review also indicates that trust has strong associations with blockchain, transparency, privacy, risk, and sustainability, reflecting its role as both a psychological and structural factor in legitimizing online transactions and fostering long-term relationships with consumers. Furthermore, this literature highlights trust as a mediator in repurchase intent and consumer engagement. This study affirms trust as a strategic foundation for the success of online markets and calls for interdisciplinary research to strengthen consumer trust in increasingly modern digital marketing.